Tacrolimus combined with corticosteroids versus Modified Ponticelli regimen in treatment of idiopathic membranous nephropathy: Randomized control trial. Issue 2 (February 2016) - Ramachandran, Raja; Hn, Harsha Kumar; Kumar, Vinod; Nada, Ritambhra; Yadav, Ashok Kumar; Goyal, Ajay; Kumar, Vivek; Rathi, Manish; Jha, Vivekanand; Gupta, Krishan Lal; Sakhuja, Vinay; Kohli, Harbir Singh
Abstract: Aim: There have been very few studies comparing cyclophosphamide (CTX) and calcineurin inhibitor based regimens in the management of non‐immunosuppressive symptomatic therapy (NIST) resistant idiopathic membranous nephropathy (IMN). The present study was aimed at comparing the efficacy and safety of tacrolimus (TAC)/steroids with cyclical CTX/steroids (Modified Ponticelli regimen (MPR)) in patients with IMN. Methods: Idiopathic membranous nephropathy patients ( n  = 70) with persistent nephrotic syndrome after at least 6 months of antiproteinuric therapy or with complications of nephrotic syndrome were equally randomized to receive TAC with oral prednisolone (TAC*) or MPR. Antibodies against m‐type phospholipase A2 receptor (PLA2 R Ab) were tested for at baseline and, at 6 and 12 months after the start of therapy. The primary end point was achievement of remission and secondary objectives were adverse effects and estimated glomerular filtration rate in both the study groups. Results: Intention‐to‐treat analysis showed that remissions at the end of 6 (74% with TAC* vs. 60% with MPR; P  = 0.30) and 12 months (71% with TAC* vs. 77% with MPR; P  = 0.78) were comparable. PLA2 R Ab titres at 6/12 months correlated with urine protein (r 0.54/0.58) and serum albumin (r −0.49/−0.53) at the end of therapy. Patients on CTX had a significantly higher risk of amenorrhea and while those on TAC had a greater risk of reversible nephrotoxicity. Conclusion: In NIST refractory IMN, both TAC* and MPR are comparable, but with different adverse effect profile. PLA2 R Ab has a very good association with proteinuria, and should be regularly monitored on clinical follow‐up. Summary at a Glance: In the randomized controlled trial, Ramachandran and colleagues showed thagt both tacrolimus combined with corticosteroids and modified Ponticelli regimen are comparable in the treatment of non‐immunosuppressive symptomatic therapy (NIST) resistant idiopathic membranous nephropathy (IMN). PLA2R Ab is significantly associated with proteinuria, and should be regularly monitored on clinical follow‐up.